An Extensible Real-time Visualization Pipeline for Dynamic Spatial Modelling - Rodrigues, Antônio José C.; Carneiro, Tiago G. S.; Andrade, Pedro R. (Journal of Information and Data Management, 2013)
This paper presents research results of an extensible visualization pipeline for real-time exploratory analysis of spatially explicit simulations. We identify software requirements and discuss the main conceptual and design issues. We propose a protocol for data serialization, a high performance monitoring mechanism, and graphical interfaces for visualization. Performance experiments show that combining multithreading and the Blackboard design pattern reduces the visualization response time by 80%, with no significant increase in memory consumption (less than 7%). The components presented in this paper have been integrated in the TerraME modeling platform for simulation of terrestrial systems.